THE EUROPEAN DIMENSION OF GLOBAL SECURITY: SIGNIFICANCE FOR UKRAINE - Bilokon, Mykhailo (Pressing Problems of Public Administration, 2021)
This article is devoted to the analysis of current EU practices in the field of ensuring global and regional security; to determining the place of countering hybrid threats as a component of the global security complex; to comparing the ability to realize the national interests of the state with the ability in the global dimension; to the search for ways to intensify Ukraine’s participation in the system of European counteraction and prevention of hybrid threats. The analysis of the current EU practices in the field of ensuring global and regional security, carried out in the article, showed that it is envisaged to look for a common European response to modern challenges in “strategic autonomy” and “resilience”, according to the EU Global Strategy. Thus, the EU members have stepped up the formation of a common institutional structure for countering global and regional threats (including hybrid ones), without giving up the advantages of the Euro-Atlantic integration process in this aspect. The place of countering hybrid threats in the complex of ensuring global security is determined by the fact that this issue is not limited to preventing only this type of possible dangers. However, de facto, any modern global threat in one aspect or another is used for their own purposes by the states that are the source of hybrid threats. Comparison of the ability to realize national interests with abilities in the global dimension showed that the main aspect of the subjectivization of the state in the world arena is its ability to concentrate on achieving positive dynamics of the country’s development, regardless of objective, subjective, internal or external conditions, including at the global level. Thus, Ukraine, not being a global player, but having equivalent global challenges to national security, should attract assistance to overcome them through intensified participation in the European system of countering and preventing hybrid threats. This requires strengthening the vector of integration in the aspect of attracting to the institutional complex of ensuring a common European security and defense policy, as well as concretizing and unifying relations with the allied states of Ukraine at the legislative level, with the consolidation of the features of such interaction.